A Combination of Embedded Markov Chain and Binomial Probability As A Tool in Sedimentary Facies Analysis - Djadjang Jedi Setiadi; Iyan Haryanto; Budi Muljana; Syaiful Alam (Indonesian Journal on Geoscience, 2022)
DOI:10.17014/ijog.9.3.291-302The methodology of facies analysis may include statistical examination to establish a local facies model. Without such examination, it is very difficult to predict the facies succession and to interpret the changes in depositional conditions from thick or complex stratigraphic sections. Based on the survey of sedimentary geologic literature in Indonesia, it is suggested that the aforementioned statistical method has relatively seldom been used in Indonesia. Such a situation may reflect a gap in information on the methodology and, accordingly, it seems imperative that there should be a re-exposition of the method. This paper presents a concise exposition of the combination of the embedded Markov Chain and binomial probability as one of the most successful statistical methods which are used in facies analysis. The results of previous studies of The Citalang Formation are used as a case study to illustrate its applications to the real geologic world.